Computational bioengineering : current trends and applications - Cerrolaza, M. (Imperial College Press ; Distributed by World Scientific Pub., 2004)
This book is a significant contribution to the state of the art in the field of computational bioengineering from the need for a living human database to meshless methods in biomechanics, from computational mechanobiology to the evaluation of stresses in hip prosthesis replacement, from lattice Boltzmann methods for analyzing blood flow to the analysis of fluid movement in long bones, among other interesting topics treated herein. Well-known international experts in bioengineering have contributed to the book, giving it a unique style and cutting-edge material for graduate students, academic.